From virtue ethics to rights ethics: Did the Reformation pave the way for secular ethics? - Vorster, Nicolaas (HTS teologiese studies, 2014)
In chapter four of his book, The unintended Reformation, Brad Gregory argues that ethical thinking since the 1500’s experienced a major shift in emphasis from the teleological concept of a ‘substantive morality of the good’ to liberalism’s ‘formal morality of rights’. He attributes it to the religious upheavals and ‘sociopolitical disruptions’ during the Reformation era. This article probes three elements of Gregory’s argument. Firstly, the article offers a critical assessment of Gregory’s depiction of the Reformation’s stance towards reason. It pays particular attention to the Reformation’s understanding of the effects of sin on the human being’s image of God, reason and the possibility for a shared social ethics. Secondly, this study scrutinises Gregory’s argument that the Reformation created an individualist notion of selfhood in contrast to the Roman Catholic communal notion of selfhood and thereby paved the way for modernism. Lastly, the discussion probes into Gregory’s claim that the Reformation’s ethical paradigm diverged radically from the Latin Christendom paradigm and that this contributed to the subjectivisation of ethics, by replacing a virtue ethics with a rights ethics.